A Pilot study on medication review program for senior citizens in the community pharmacy setting - Briones, June Elaine L.
Medication review is an important component of healthcare especially in elderly people, Medication review provides a unique opportunity for pharmacists to apply their knowledge in order to directly benefit the people, and to promote their role as the health system's medication expert. This study aimed to develop, implement and evaluate a comprehensive community based medication review program among the senior citizens. This study consisted of three phases namely; planning and creation, implementation and evaluation of the medication review program. The program was implemented in a single community pharmacy at Las Piňas City. Evaluation consisted of a survey among senior citizens and pharmacists to assess their perception, level of acceptance and barriers to the conduct of the program. The medication review program identified 64 (53.78%) out of 119 senior citizen customers with potential drug interactions. The most common medications used are those indicated for hypertension, diabetes, and hypercholesterolemia. Of the 64 customers, only 8 participated in the interview. The interview with the customer revealed that all have at least one medication not taken on the recommended time and probable drug interaction. The participants perceive the program as an important service to promote better understanding of medicines and diseases. Time was only barrier perceive to their participation. Community pharmacists, on the other hand, agreed that medication review program is a necessary service for the patients to improve poor or ineffective use of medicine . They perceived financial incentive, suitable working area, lack of access to costumer's medical records and the appropriate resources as barriers to conduct medications review. In conclusion, the medication review program is highly acceptable among customers and pharmacists, and thus, must be conducted in the community setting.